Agenesia de bazo, situs inversus y cardiopatía congénita (Síndrome de Ivemark). Presentación de un caso. - Borbolla, Liane; Dueñas, Enzo; Bellas, Eduardo; Pereiras, Rolando; Pérez Martínez, Rafael (Revista Cubana de Pediatría, 2022)
Presentación de un caso.